Nivel de conocimientos sobre ESAVI en estudiantes de enfermería de la Universidad Nacional de Loja - Paccha Quizhpe, Jhuliana Anabel (2023)
Immunization is considered one of the greatest achievements of public health worldwide, since it has significantly decreased the incidence of communicable diseases. However, its use may be accompanied by unintended adverse reactions known as ESAVI, which is any unfavorable clinical event that occurs after vaccination or immunization and that does not necessarily have a causal relationship with the vaccination process or with the vaccine. The objective of the research was to identify the sociodemographic characteristics of nursing students at the National University of Loja, as well as the level of knowledge about Events Supposedly Attributable to Vaccination and Immunization in order to develop an intervention plan on feedback on the subject. from ESAVI. The study was quantitative-descriptive-cross-sectional, with a convenience sampling technique of 125 students, where inclusion and exclusion criteria were taken into account, as well as their respective ethical considerations. The data collection instrument was a survey validated using the Cronbach's alpha reliability test, where, once the data was obtained, they were tabulated using the statistical program SPSS V21. For their respective analysis and interpretation, the use of tables was considered, where it was shown that 76.8% of the student population corresponds to the female sex, 77.6% comprises the age range of 20 to 23 years, and 32 0.0% belongs to the eighth cycle of the career. Regarding the level of knowledge that they possess, it was evidenced that 70.4% of the total population has a medium level, 18.4% of the students have a high level, and the remaining 11.2% have a low level. of knowledge about ESAVI. Therefore, it is concluded that the majority of the student population has an average knowledge about ESAVI